THE ACCOUNTABILITY OF VILLAGE FUNDS AND INTERNAL CONTROL - Asmara Br Barus, Agatha Amorenyta; Hariwibowo, Ignatius Novianto (Widya Mandala Surabaya Catholic University, 2024)
Research Purposes. This study aims to examine the variables that affect accountability for village fund management in Kedu District. The role and competence of village apparatus are the factors tested in this study, with the internal control system as the moderating variable.Research Methods. To get the results, this study selected village device respondents based on the purposive sampling method. The results of 132 respondents were involved in this study. The data obtained is processed using Partial Least Square (PLS).Research Results and Findings. This research reveals that the role of village apparatus has no influence on the accountability of village fund management. Meanwhile, the competence of village apparatus has a positive influence on the accountability of village fund management. In addition, in the context of moderation, the internal control system has an influence on the role of village apparatus and accountability of village fund management. Meanwhile, the internal control system cannot affect the relationship between the competence of village apparatus and accountability of village fund management.